Characterization of a diversity panel to obtain promising materials with high carbon sequestration capacity. - Posso Hernandez, Sylvana (2023)
Plants have the ability to take CO2 from the atmosphere and store it in their leaves, stems and roots. Part of the carbon is transferred to the soil through the root system and stored as organic carbon (COS), which is key to global warming mitigation processes. Therefore, the Alliance Bioversity International & CIAT rice program is evaluating and characterizing a diversity panel of 205 materials through the measurement of morphological, disease resistance, physiological, quality and yield related traits. The ﬁnal goal is to develop rice varieties with high carbon sequestration capacity that fulﬁll the requirements of the farmers facilitating the adoption and dissemination.